Perancangan Aplikasi Surat Perintah Perjalanan Dinas (SPPD) Responsive with Bootstrap Berbasis Web - Hendry; Eka Putra; Muhammad Zen; Supiyandi; Chairul Rizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Good management in conducting business trips has a positive effect on employees who take business trips and also on the smooth operation of the company. There are so many business travel destinations that are financed directly by the company such as: Business visits, parties, general meetings, educational and training activities as well as socialization. The method used by the author in this study is the Waterfall method which consists of: Requirements, Design, implementation, Verification and Maintenance. The result of this research is to produce an information system for official travel orders that will assist employees in the process of submitting a letter of assignment and the process of calculating official travel costs.